Dermoscopic features of uncomplicated tinea versus steroid-modified tinea: An observational study in Indian patients - Gadekar, Mithila Ninad; Syed, Nausheen; Chate, Ashutosh; Save, Sushrut (UI Scholars Hub, 2021)
Background: Tinea is one of the most common superficial fungal skin infections. Steroid-modified tinea infections may present with atypical morphology. This study aims to observe the difference between dermoscopic features of uncomplicated dermatophytosis and steroid-modified dermatophytosis.Methods: This observational study was conducted in 60 patients with tinea cruris, tinea corporis and tinea faciei in the outpatient dermatology department of a tertiary care center. Patients were divided into group A and group B. Group A included 30 patients with no history of steroid use in the past three months. Group B included 30 patients with a history of steroid usage in the past three months. Dermoscopy was performed in both groups using a USB 2.0 dermoscope (Dino-Lite Premier AM3113T®, Magnification – 20x to 50x and 200x) to study the characteristic features in tinea infections. Chi-square test and Fisher’s exact test were applied as applicable.Results: Out of 60 cases of dermatophytosis, 20 cases were of tinea corporis, 28 cases of tinea cruris, and 12 cases of tinea faciei. Dermoscopic features of hair follicular involvement (perifollicular scale, follicular micropustules, the involvement of vellus hair, yellow hair, morse code hair, and transparent hair) were significantly more common in group B than in group A (P = 0.004, P = 0.039, P = 0.0001, P = 0.01, P = 0.03, P = 0.002, respectively for each feature).Conclusions: All dermatophytosis patients with a history of steroid use showed characteristic signs on dermoscopic examination irrespective of their morphologic appearance. Thus, dermoscopy can be used as a rapid diagnostic method for steroid-modified cases of tinea.